P232 EXERTIONAL BREATHLESSNESS IN HYPERTROPHIC CARDIOMYOPATHY: OBSTRUCTION–INDEPENDENT SYMPTOMS IN A "PARADOXICAL" RESPONSE TO EXERCISE. (18th May 2022) - Baratto, C; Caravita, S; Crotti, L; Villella, F; Rella, V; Cecchi, F; Badano, L; Parati, G; Perego, G
Abstract: A 66–y.o. man with hypertrophic cardiomyopathy presented with residual exertional dyspnea NYHA III a few years after surgical myectomy, mitral valve repair and ICD implantation. Echocardiography showed residual mild septal hypertrophy and mitral regurgitation (MR), and a variable obstruction of left ventricular outflow tract (LVOT), witnessed by a pressure gradient ranging from 15 to 50–70 mmHg (Figure 1 ). Exercise echocardiography did not suggest exercise–induced LVOT obstruction (LVOTO) or functional MR. We thus performed a thorough invasive hemodynamic evaluation at rest and during exercise. LVOTO was present at rest, with a maximum pressure gradient of 90–100 mmHg and typical "spike–and–dome" configuration of the aortic pulse contour (Figure 2 ), with LV end–diastolic pressure (LVEDP) at the upper limit of normal (15 mmHg) and normal pulmonary hemodynamics. During exercise, we observed a paradoxical reduction of the LVOTO (30–40 mmHg at peak, Figure 2 ). Pulmonary hypertension developed during exercise, due to LV diastolic dysfunction, witnessed by a marked increase in pulmonary artery wedge pressure and LVEDP (up to 25 mmHg and 30 mmHg at peak, respectively). Cardiac output (CO) reserve was at the lower limits of normal, mainly due to chronotropic incompetence, responsible for a mildly reduced exercise capacity (peak oxygen consumption was 20 mL/Kg/min, 75% of predicted). Thus, cardiac catheterization confirmed the presence of a relevant LVOTO at rest, that was not directly related to exertional symptoms. These latter were mainly attributable to LV diastolic dysfunction and reduced CO reserve. These findings helped us driving treatment decision in a tailored way: beta–blockers were not uptitrated, because of their negative inotropic effect, and high–risk septal reduction therapies were excluded, since exertional symptoms were unrelated to LVOTO. However, an attempt to reduce LVOTO was done by DDD sequential pacing through the ICD. Pacing could induce mechanical dyssynchrony and reduce LVOTO by increasing the end–systolic LVOT diameter. The simultaneous echocardiographic monitoring highlighted an acute reduction of LVOT gradient from 50–70 mmHg to 20–30 mmHg (Figure 3 ). This case suggests that, in well–selected cases, patients' management based on pathophysiological reasoning may help to define the etiopathogenetic mechanism underlying symptoms, and to drive treatment decision in a patient–centered way.